THE PREVALENCE OF PROSTATE CANCER DIAGNOSTIC TESTS IN A RURAL COMMUNITY - Rosana Amora Ascari; Scheila Pelissari; Márcia Danieli Schmitt; Olvani Martins da Silva; Eliana Buss; Tania Maria Ascari (Universidade Federal do Paraná, 2014)
This descriptive study with a quantitative approach aimed to identify the prevalence of preventive tests for prostate cancer in men aged over 40 years old, resident in the community of Videira in the interior of the State of Santa Catarina. The whole population of the community was mapped, totalling 210 individuals; of these, 70 men met the inclusion criteria. The data were collected using a questionnaire. It was determined that 61.8% of the men knew about the tests for preventing prostate cancer; 41.1% had undertaken the tests and 58.9% had not, stating the cause to be lack of knowledge, not considering it to be necessary, and not presenting symptoms. It was possible to outline a plan of educational actions in the community regarding prostate cancer, suggesting greater attention in the approach to the health of the male population.